Identifying The Narrator of Hadith in The Critism of Sanad - Jannah Lukman (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2020)
The Prophetic Hadith has been criticized by sanad and isnad analyzing.In this study, the author explained the narrators of Hadith identity needed based on ‘Ilmu rijāl al-Hadīś. This study aimed to identify the narrators of Hadith correctly and identify their biography objectively to prevent and avoid misidentify in sanad. This process of analyses aims to win sanad quality. This research is a qualitatve study using analytical description to explain the resources. The primary data used in this study is a book the so-called ‘Ulūm al- Hadīś. The research found out many aspects are pivotal for considerations in identifyng the rawi when someone wants to quote his hadith, such as ensuring the name, nasab, nisbah, kuniah, maula, mutasyābih, mubham, laqab, teacher and student, rihlah, tarikh, and thabaqat. This research alsofound the book of the narrator’s biography resourches to help the process of identifications